Racial Differences in Trajectories of Heavy Drinking and Regular Marijuana Use from Ages 13 through 24 Among African-American and White Males - Finlay, Andrea K. (2011)
BACKGROUND: Although there are significant differences in prevalence of substance use between African-American and White adolescents, few studies have examined racial differences in developmental patterns of substance use, especially during the important developmental transition from adolescence to young adulthood. This study examines racial differences in trajectories of heavy drinking and regular marijuana use from adolescence into young adulthood. METHODS: A community-based sample of non-Hispanic African-American (n = 276) and non-Hispanic White (n = 211) males was analyzed to identify trajectories from ages 13 through 24. RESULTS: Initial analyses indicated race differences in heavy drinking and regular marijuana use trajectories. African Americans were more likely than Whites to be members of the nonheavy drinkers/nondrinkers group and less likely to be members of the early-onset heavy drinkers group. The former were also more likely than the latter to be members of the late-onset regular marijuana use group. Separate analyses by race indicated differences in heavy drinking for African Americans and Whites. A 2-group model for heavy drinking fit best for African Americans, whereas a 4-group solution fit best for Whites. For regular marijuana use, a similar 4-group solution fit for both races, although group proportions differed. CONCLUSIONS: Within-race analyses indicated that there were clear race differences in the long-term patterns of alcohol use; regular marijuana use patterns were more similar. Extended follow ups are needed to examine differences and similarities in maturation processes for African-American and White males. For both races, prevention and intervention efforts are necessary into young adulthood.